Building Independent Villages through Collaborative Governance by Village-Owned Enterprises (Best Practice from Panggungharjo Village, Central Java, Indonesia) - Sri Juni Woro Astuti; Falih Suaedi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2018)
This study aims to develop a collaborative governance model applied by village-owned enterprises called